Impacts of Soil Conditioners and Water Table Management on Phosphorus Loss in Tile Drainage from a Clay Loam Soil. Issue 2 (1st March 2015) - Zhang, T. Q.; Tan, C. S.; Zheng, Z. M.; Welacky, T. W.; Reynolds, W. D.
Abstract : Adoption of waste‐derived soil conditioners and refined water management can improve soil physical quality and crop productivity of fine‐textured soils. However, the impacts of these practices on water quality must be assessed to ensure environmental sustainability. We conducted a study to determine phosphorus (P) loss in tile drainage as affected by two types of soil conditioners (yard waste compost and swine manure compost) and water table management (free drainage and controlled drainage with subirrigation) in a clay loam soil under corn–soybean rotation in a 4‐yr period from 1999 to 2003. Tile drainage flows were monitored and sampled on a year‐round continuous basis using on‐site auto‐sampling systems. Water samples were analyzed for dissolved reactive P (DRP), particulate P (PP), and total P (TP). Substantially greater concentrations and losses of DRP, PP, and TP occurred with swine manure compost than with control and yard waste compost regardless of water table management. Compared with free drainage, controlled drainage with subirrigation was an effective way to reduce annual and cumulative losses of DRP, PP, and TP in tile drainage through reductions in flow volume and P concentration with control and yard waste compost but not with swine manure compost. Both DRP and TP concentrations in tile drainage were well above the water quality guideline for P, affirming that subsurface loss of P from fine‐textured soils can be one critical source for freshwater eutrophication. Swine manure compost applied as a soil conditioner must be optimized by taking water quality impacts into consideration.